The impact of physical activity to the child’s quality of life: a bibliometric study [version 1; peer review: 1 approved, 2 approved with reservations] - Jernej Završnik; Peter Kokol; Helena Blažun Vošner (F1000Research, 2019)
Background: The application of bibliometrics in healthcare research is becoming popular, however at present it is still an under-researched area. Methods: In our study we used a bibliometric technique called bibliometric mapping to visualize the published research regarding the influence of physical activity to children’s quality of life. The research was visualized in the form of both chronological and cluster science landscapes. Science landscapes, contrary to conventional reviews, capture the relationships between multiple topics and concepts, enabling the generation of “synthetic reviews”. Results: Evolutionarily, three distinct research phases appeared, namely research on influence of physical activity on various chronic non-communicable diseases; research on quality of life and childhood diseases related to physical activity; and outcome-related research. The research consists of six main topics: asthmatic child and exercising, blood diseases, health-related quality of life, obesity and chronic diseases, childhood obesity and behaviour, and depression and health outcomes. Conclusions: The study identified some research that may be helpful to general paediatricians whose everyday practice or research is not focused on physical activity and child’s quality of life, but wants to learn about the taxonomy of the topics, the most interesting discoveries, guidelines and practices and the state of the art in the field. It also revealed some hidden association, otherwise not easily identified, even by informed researchers and clinicians.